Anxiety and Attentional Processes: The Role of Resting Heart Rate Variability - Giuseppe Forte; Francesca Favieri; Esther Osariemen Oliha; Andrea Marotta; Maria Casagrande (Brain Sciences, 2021)
Individuals with high anxiety preferentially focus attention on emotional information. The autonomic nervous system (ANS) plays an important role in modulating both anxiety and attentional processes. Despite many studies having evaluated attentional bias in anxious people, few of them have investigated the change blindness phenomenon associated with the attentional response toward salient stimuli, considering the role of the ANS. This study aimed to examine the role of heart rate variability (HRV) in trait anxiety and top-down and bottom-up attentional processes toward emotional stimuli. Seventy-five healthy university students were divided into high (N = 39) and low (N = 36) trait anxiety groups and completed a change detection flicker task with neutral, positive, and negative stimuli. The results evidenced a different attentional pattern between people with high and low anxiety considering both the two attentional processes and the valence of the stimuli. Specifically, individuals with high anxiety showed a bias in elaborating emotional stimuli related to their salience (i.e., negative stimuli were faster elaborated than neutral and positive stimuli when top-down attentional mechanisms were involved, while slower performances were highlighted considering bottom-up attentional mechanisms in response to emotional stimuli compared to neutral stimuli). Moreover, an association between HRV, trait anxiety levels, and change blindness phenomenon was confirmed. These results underline the role of HRV as a possible predictor of the alteration of attentional mechanism in anxiety.